Machine Learning(s) in gaming disorder through the user-avatar bond: A step towards conceptual and methodological clarity - Stavropoulos, Vasileios; Prokofieva, Maria; Zarate, Daniel; Colder Carras, Michelle; Ratan, Rabindra; Kowert, Rachel; Schivinski, Bruno; Burleigh, Tyrone L; Poulus, Dylan; Karimi, Leila; Gorman-Alesi, Angela; Brown, Taylor; et al. (Journal of behavioral addictions, 2024)
In response to our study, the commentary by Infanti et al. (2024) raised critical points regarding (i) the conceptualization and utility of the user-avatar bond in addressing gaming disorder (GD) risk, and (ii) the optimization of supervised machine learning techniques applied to assess GD risk. To advance the scientific dialogue and progress in these areas, the present paper aims to: (i) enhance the clarity and understanding of the concepts of the avatar, the user-avatar bond, and the digital phenotype concerning gaming disorder (GD) within the broader field of behavioral addictions, and (ii) comparatively assess how the user-avatar bond (UAB) may predict GD risk, by both removing data augmentation before the data split and by implementing alternative data imbalance treatment approaches in programming.
Keywords: uživatelské rozhraní počítače; avatar; Avatar; Machine Learning; netholismus; Supervised Machine Learning; videohry; Humans; Video Games; strojové učení; řízené strojové učení; lidé; Internet Addiction Disorder; User-Computer Interface